From the LOGSE to the quality law (Journal of Parents and Teachers, 2014)
Political parties regulate and control the education of our society. This article offers a tour of the educational legislation of recent years in our country, focusing on the LOGSE (organic educational law from the PSOE) and the subsequent alternative LOCE (educational bill proposed by the PP).
Keywords: political parties; educative legislation; LOGSE; LOCE